Relationship between Leptin and Migraine - Sana Javaid, Jazib Andleeb, Amina Ahmed, Hassan Touqeer, Ghazal Mansoor, Syed Iqtadar Ali Rizvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: to assess the relationship and association between levels of leptin in serum and the risk of migraine. Study Type: cross-sectional study Study Place and Duration: from 1st January 2021 to 1st January 2022, at Sharif Medical and Dental College, Lahore. Material and methods: Total 626 individuals were randomly selected aged between 35-75 years, during the period of 2021-2022. After minimum fasting of 8 hours the blood samples are obtained along with calculation of body weight and height are calculated. At 8oC samples were stored and transported to laboratory on dry ice. Leptin and adiponectin levels (serum) are calculated using ELISA (enzyme-linked immunosorbent assay) Using GDA (glucose dehydrogenase assay). The relation between the migraine diagnosis and the leptin levels was calculated by the usage of BLRA (binary logistic regression analysis). < 0.05 (p-value) was taken to be important. With the help of SPSS v.21 the statistical analyses were undertaken. Results: There were no statistical difference was found in age, gender, BMI, glucose status and adiponectin in both the groups. Lifetime, major depressive disorder was higher in migraine group than controls as 197 (62.9%) and 141 (45.0%), respectively, (p=0.000). Regular intake of antidepressants was also higher in migraine group 53 (16.9%) and lower in controls 35 (11.1%), (p=0.038). Similarly, the average leptin was higher than that of control group as 13.23±2.66ng/mL and 15.07±4.21ng/mL, respectively, (p=0.000). (Table. I). Conclusion: The results of this study suggest that high levels of leptin are associated with risk of migraine.